2017
DOI: 10.4149/bll_2017_133
|View full text |Cite
|
Sign up to set email alerts
|

Periostin normalizes levels of cardiac markers in rats with experimental isoproterenol cardiotoxicity

Abstract: It is concluded that periostin could have a potential to increase the rate of myocardial recovery after myocardial infarction (Tab. 5, Ref. 28).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Periostin was found to be involved in tissue repair after vascular injury, e.g., in acute rheumatic fever [ 28 ], hypertensive nephropathy [ 19 ], myocardial infarction [ 47 ], and subarachnoid hemorrhage [ 48 ]. Periostin plays a critical role in the interaction with signaling proteins such as NF-kB (nuclear factor kappa B) or STAT3 (signal transducer and activator of transcription) to modulate the response of the extracellular matrix in various tissue pathologies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periostin was found to be involved in tissue repair after vascular injury, e.g., in acute rheumatic fever [ 28 ], hypertensive nephropathy [ 19 ], myocardial infarction [ 47 ], and subarachnoid hemorrhage [ 48 ]. Periostin plays a critical role in the interaction with signaling proteins such as NF-kB (nuclear factor kappa B) or STAT3 (signal transducer and activator of transcription) to modulate the response of the extracellular matrix in various tissue pathologies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al found that overexpression of periostin in obese rats resulted in liver steatosis and hypertriglyceridemia via activation of c-Jun N-terminal kinase (JNK) signaling pathway and downregulation of peroxisome proliferator-activated receptor alpha (PPARα) [ 60 ]. On the other hand, a recent interventional study in rats after myocardial infarction showed a beneficial effect of periostin supply on HDL-cholesterol [ 47 ]. These experimental results suggest the positive impact of the studied particle on the regulation of cholesterol and triglycerides levels.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 30 male, 10 weeks old BALB/c mice (Kobay Inc, TR) weighing 30 ± 3.59 g were randomly divided into three groups, each consisting of 10 mice. The conditions of the cage environment, care, and feeding of the animals were designed as previously reported (9).…”
Section: Animals and Husbandrymentioning
confidence: 99%
“…The obtained homogenates were centrifuged at 3000 rpm for 5 minutes at +4 °C. Oxidative stress parameters were measured in supernatants formed after a centrifugation (9). The levels of Total Antioxidant Status (TAS) and Total Oxidant Status (TOS) in liver and kidney tissue homogenates were measured spectrophotometrically (MultiskanGO, Thermo, USA) using the methods described in the kits (Rel Assay Kit Diagnostics, TR).…”
Section: Biochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation